The ANALYSIS OF PARENT PARTICIPATION ON VIRTUAL LEARNING - Yuli Sugiarti (Jurnal Jendela Bunda Program Studi PG-PAUD Universitas Muhammadiyah Cirebon, 2021)
Parental participation is all forms of parental involvement and participation in children's education and learning that can support good learning. Parents have a very important role in the education of their children. Especially in conditions of learning that must be done virtually. Virtual learning is learning that is carried out remotely or PJJ. This certainly requires the participation of parents to work together in realizing conducive and effective learning. In this study, the researcher wanted to know the effect of parental participation on virtual learning in PAUD institutions in Waluran District with the research subject being parents who have children aged 5-6 years who are group B students. This study uses a quantitative survey method by conducting a Pearsson correlation coefficient test. , it is shown that the value of R is a positive value and the coefficient of determination is calculated which shows a value of 43.3%, meaning that the Y variable has a 43.3% effect on the Y variable.